THE EFFECT OF NUMBERED HEADS TOGETHER (NHT) LEARNING METHODS ON COMMUNICATION SKILLS OF STUDENTS IN CLASS IV ELEMENTARY SCHOOL - Novibriawan, Fedik; Nurhasanah, Nurhasanah; Karma, I Nyoman (PROGRES PENDIDIKAN, 2021)
his study aims to determine the effect of the Numbered Heads Together type of cooperative learning model on students' communication skills in class IV social studies content at SDN Gugus 01 Pringgarata District, Central Lombok in 2018/2019 academic year. This research is an experimental study of the type of Quasi-Experimental Design Type of Nonequivalent Control Group Design. The sampling technique used is Purposive Sampling, which considers all kinds of aspects in determining the sample. The method of data collection is observation in the form of student observation sheets or direct observations and rubrics as a reference for assessment. The data obtained were then analyzed using the t-test polled variance formula to determine the effect of the use of the Numbered Heads Together type of cooperative learning model on students' communication skills. Based on the post-test results, the average value of students' communication skills in the experimental class was 75.9 and the control class was 67.8. The results of the t-test calculation obtained that the t-count value is greater than t-table namely, the t-count value is 2.84 while the t-table is 2.006 at a significance level of 5%. Thus, it can be concluded that Ha is accepted and Ho is rejected, which means that there is a positive and significant effect between the Numbered Heads Together type of cooperative learning model on students' communication skills in social studies content for class IV SDN Gugus 01 Pringgarata sub-district, Central Lombok in the 2018/2019 academic year.